HARD SCIENCE TEACHING: THE STUDY OF US EXPERIENCE AND ITS IMPLEMENTATION IN KAZAKHSTAN EDUCATION - Tuktubayeva, S. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
This article discusses the results of a study conducted as part of the Bolashak internship from May to October 2022. The purpose of this study was to study the experience of teaching subjects of the natural and mathematical cycle in US schools and introduce positive experience into the practice of Kazakh teachers. The relevance of this study lies in the fact that with the expansion of cooperation between different countries in the field of science, it is necessary to develop a unified approach to learning and teaching.
Keywords: science-mathematical cycle subjects; teaching experience; research; Kazakh teachers; teaching